2015
DOI: 10.1016/j.cell.2015.07.036
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Bicycle Model for Circadian Clock Control of Membrane Excitability

Abstract: Summary Circadian clocks regulate membrane excitability in master pacemaker neurons to control daily rhythms of sleep and wake. Here we find that two distinctly timed electrical drives collaborate to impose rhythmicity on Drosophila clock neurons. In the morning, a voltage-independent sodium conductance via the NA/NALCN ion channel depolarizes these neurons. This current is driven by the rhythmic expression of NCA localization factor-1, linking the molecular clock to ion channel function. In the evening, basal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
235
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(254 citation statements)
references
References 63 publications
16
235
3
Order By: Relevance
“…Modeling work using data from the action potential clamp also emphasizes the role of the Na þ leak in driving excitability in SCN neurons (Clay 2015). A recent experimental advance has been the description of a voltage-independent Na þ conductance via the NA/NALCN ion channel, which depolarizes both SCN neurons and Drosophila pacemaker neurons (Flourakis et al 2015). This study represents a significant advance as it provides the first evidence for the circadian regulation of an Na þ current.…”
Section: Daily Depolarizationmentioning
confidence: 91%
See 1 more Smart Citation
“…Modeling work using data from the action potential clamp also emphasizes the role of the Na þ leak in driving excitability in SCN neurons (Clay 2015). A recent experimental advance has been the description of a voltage-independent Na þ conductance via the NA/NALCN ion channel, which depolarizes both SCN neurons and Drosophila pacemaker neurons (Flourakis et al 2015). This study represents a significant advance as it provides the first evidence for the circadian regulation of an Na þ current.…”
Section: Daily Depolarizationmentioning
confidence: 91%
“…In Drosophila, circadian rhythms in mRNA encoding a regulatory protein associated with BK channels have been described (McDonald and Rosbash 2001;Duffield 2003). A recent study from the Allada laboratory (Flourakis et al 2015) showed that the circadian clock regulates excitability via an Na þ leak conductance (as described above). This sodium leak current depends on the expression of nonspecific crossreacting antigen (NCA) localization factor 1.…”
Section: How the Molecular Clockwork Regulates Neural Activity?mentioning
confidence: 99%
“…Contributing to this rhythm is a sodium leak current mediated by NA that recently has been shown to depolarize Drosophila clock neurons (22 push the neurons into the more depolarized daytime state, eliminating the acute day/night differences in all cases ( Fig. 2 and Table S3).…”
Section: Mp (Mv)mentioning
confidence: 99%
“…Membrane potential is important for control of circadian behavior, and manipulation of Shaw and the Narrow Abdomen (NA) channels, both of which are expressed and function within clock neurons influence neuronal electrical activity, the circadian clock, and clockcontrolled behavior in both flies (20)(21)(22) and mice (23)(24)(25). The firing rate is a key component in mammalian circadian rhythmicity and can be regulated by regional and circadian expression of the sodium potassium chloride cotransporter NKCC, which switches the effects of GABA from inhibitory to excitatory across the day (26,27).…”
mentioning
confidence: 99%
“…Blue-lightactivated CRY couples to membrane depolarization in Drosophila LNv neurons by a redox-based mechanism involving potassium channel heteromultimeric complexes, consisting of the downstream redox sensor cytoplasmic potassium beta (Kvβ), HYPERKINETIC (HK), and ion-conducting voltage-gated potassium alpha (Kvα) ether-a-go-go family subunits (8). Electrical activity in the LNvs contributes to circadian rhythms (9)(10)(11), and, reciprocally, LNv neuronal firing rate is circadian-regulated (1,2,12). Circadian regulation of firing rate is widely conserved in other invertebrate and vertebrate species (13,14).…”
mentioning
confidence: 99%